Vacuum Preconsolidation Settlement Characteristics and Microstructural Evolution of Marine Dredger-Filled Silt. (22nd June 2021) - Chen, Keping; Ren, Xinkai; He, Yong; Gan, Muyuan; Wu, Danwei; Chen, Lianwei
Abstract : The method of vacuum preloading for foundation treatments is used in the construction of the Fangchenggang coastal area in Guangxi province, China. The thick marine dredger-filled silt has a considerable impact on the treatment effort. In this study, the mineral composition and grain size distribution of these silts were analyzed to investigate their consolidation settlement property and microstructures. The scanning electron microscope and finite element method were adopted. The results reveal that the dredger-filled silt in this area is composed mainly of sand with particle size mostly smaller than 0.075 mm. To replicate the construction process, the process of drainage by the vacuum preloading method was simulated by setting different water levels in the finite element analysis. The displacement and the dissipation of the pore water pressure obtained by simulations were reasonably consistent with the field monitoring data. In addition, the results obtained using the scanning electron microscope indicate that the equivalent diameter of the structural unit and that of the pore unit decrease with the silt depth. However, the value of the structural abundance approaches one, whereas the pore abundance is significantly different from one.